(untitled) (Third Sector Social Economic Review, 2020)
The main purpose of this study is to research intermediary role of openness to organizational change in the impact of perceived organizational support on job performance. Research has been done towards higher unit employees of agriculture sales cooperative being active in Marmara ve Ege region. Total 495 persons have participated in the research. The survey method was used for collection of data. It is determined that perceived organizational support has a positive and meaningful effect on job performance and openness to change. In the research, total effect value, direct effect value and indirect effect value have been found as 0.193, 0.187 and 0.007, respectively. According to other result of research, due to including zero value of bootstrap confidence intervals, it is determined that perceived organizational support isn’t intermediary role of openness to change in the impact of job performance.